Predictive ability of obesity- and lipid-related indicators for metabolic syndrome in relatively healthy Chinese adults - Duan, Yuting; Zhang, Weiguang; Li, Zhe; Niu, Yue; Chen, Yizhi; Liu, Xiaomin; Dong, Zheyi; Zheng, Ying; Chen, Xizhao; Feng, Zhe; Wang, Yong; Zhao, Delong; et al. (Frontiers in Endocrinology, 2022)
Background & Objective: Metabolic syndrome (MetS) is an important risk factor for cardiovascular complications and kidney damage. Obesity- and lipid-related indices are closely related to MetS, and different indices have different predictive abilities for MetS. This study aimed to evaluate the predictive value of 8 obesity- and lipid-related indicators, including body mass index (BMI), lipid accumulation product (LAP), body roundness index (BRI), Chinese visceral adiposity index (CVAI), body adiposity index (BAI), abdominal volume index (AVI), triglyceride glucose index (TYG), and visceral adiposity index (VAI), for MetS. Methods: A total of 1452 relatively healthy people in Beijing were enrolled in 2016, and the correlation between the eight indicators and MetS was analyzed by multivariate logistic regression. The receiver operating characteristic (ROC) curve and area under the curve (AUC) were used to analyze the predictive ability of eight indicators for MetS. The Delong test was used to compare the AUC values of the eight indicators. MetS was defined according to the Chinese Guidelines for the Prevention and Treatment of Type 2 Diabetes (2020 Edition), the revised National Cholesterol Education Program Adult Treatment Group (NCEP-ATPIII) and the International Diabetes Federation (IDF). Results: Using these three sets of criteria, LAP, TYG, CVAI and VAI, which are based on blood lipids, had higher AUC values for MetS prediction than BMI, BRI, AVI and BAI, which are based on anthropometry. LAP had the highest AUC values of 0.893 (0.874-0.912), 0.886 (0.869-0.903), and 0.882 (0.864-0.899), separately, based on three sets of criteria. Conclusion: The eight obesity- and lipid-related indicators had screening value for MetS in relatively healthy people, and of the eight, LAP performed the best.